PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA GURU (Studi Kasus di Guru MA di Kecamatan Margoyoso Kabupaten Pati) - Susanto, 1352020081; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This researchâs purpose is to find and examine the effect of professional competency and work motivation towards teacherâs performance in mediation of workâs satisfaction which is taken from MA teacher in Margoyoso sub district, in Pati regency, as the object. This research is an explanatory research, which is aiming for explaining relevant variables with phenomena that being observed, this research also called population study or census study. Population that being used in this research is 143 teachers. Data testing in this research consists of validity test with factor analysis and reliability test with alpha cronbach formula. Before analyzing the data, the requirements examination is needed through classic assumption test, such as: normality test, multi co-linear test,Â  heterosketastisitas test , and double linear regression test to find whether the dependent and independent variable are influencing each others or not, determination coefficient to find how many effects of dependent variable towards independent variable, t-test to find the modelâs expediency, hypothesis test to find whether the hypothesis is acceptable or not, and also mediation regression test. The researchâs result shows that the professional competency has positive effect and significant towards work satisfaction. Work motivation variable has positive effect and significant towards work satisfaction. Professional competency doesnât have positive effect and insignificant towards teacherâs performance. Work satisfaction mediating the effect between professional competency towards teacherâs performance, and work satisfaction mediating the effect between work motivation towards teacherâs performance. Keywords: Professional Competency, Work Motivation, Work Satisfaction, and Teacherâs Performance.